Alcohol-Based Chlorhexidine and Potassium Sorbate Rub Strengthens the Effectiveness of Traditional Hand Scrubbing and Improves Long-Lasting Effectiveness-Evaluation of Hand Preparation Protocols According to EN 12791 - Elena Herráiz Soria; Luis Alou; Carlos Martin-Villa; Ricardo Becerro-; Marta Losa-Iglesias; David Sevillano (MDPI AG, 2024)
Despite the advantages of surgical handrub in terms of the ease of application and effectiveness, chlorhexidine (CHG)-based hand scrubbing remains the preferred method for surgical hand preparation. However, it does not systematically meet the non-inferiority requirement of the European norm (EN) 12791 with respect to n-propanol (the reference product) and does not provide the sustained efficacy expected for these long-lasting agents. Commercially available alcohol-based products have also failed to demonstrate sustained efficacy according to EN 12791. Multi-step protocols enhance the efficacy of hand scrubbing, yet their extended disinfection duration might diminish their allure for healthcare professionals. In this study, we show that hand scrubbing with CHG 4% followed by a 1 min rubbing with the novel formulation of ethanol (Et) 70%/CHG 3% plus 0.3% potassium sorbate food additive (PS) meets the non-inferiority requirement and demonstrates sustained efficacy when tested according to EN 12791. The immediate and 3 h effect of this protocol was significantly higher than that of n-propanol and the homologous disinfection protocol without PS (CHG 4% hand scrub plus Et 70%/CHG 3% rub), demonstrating that the inclusion of PS confers a notable residual effect. We speculate that this non-volatile ingredient acts synergistically with CHG. This promising combination represents an alternative method for the development of new disinfection strategies.